Characterising scoring rules by their solution in iteratively undominated strategies - Christian Basteck (Economic Theory, 2022)
We characterize voting procedures according to the social choice correspondence they implement when voters cast ballots strategically, applying iteratively undominated strategies. In elections with three candidates, the Borda Rule is the unique positional scoring rule that satisfies 'unanimity' (U) (i.e., elects a candidate whenever it is unanimously preferred) and is 'majoritarian after eliminating a worst candidate' (MEW)(i.e., if there is a unanimously disliked candidate, the majority-preferred among the other two is elected). In a larger class of rules, Approval Voting is characterized by a single axiom that implies both U and MEW but is weaker than Condorcet-consistency (CON)—it is the only direct mechanism scoring rule that is 'majoritarian after eliminating a Pareto-dominated candidate' (MEPD)(i.e., if there is a Pareto-dominated candidate, the majority-preferred among the other two is elected); among all finite scoring rules that satisfy MEPD, Approval Voting is the most decisive. However, it fails a desirable monotonicity property: a candidate that is elected for some preference profile, may lose the election once she gains further in popularity. In contrast, the Borda Rule is the unique direct mechanism scoring rule that satisfies U, MEW and 'monotonicity' (MON). There exists no direct mechanism scoring rule that satisfies both MEPD and MON and no finite scoring rule satisfying CON.
Keywords: C72; D71; D72; 300; sophisticated voting; iterated weak dominance; majoritarianism; scoring rules; Borda rule; approval voting